IMPLEMENTASI KEBIJAKAN PROGRAM PENGENDALIAN TERNAK DI KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Maspada, Dikwan Herman; Tjaija, Abu; Alamsyah, M. Nur (Katalogis, 2019)
This research is about the implementation of livestock control program policies in Sigi Regency, Central Sulawesi Province. This type of research is descriptive, with the number of informants as many as 7 people, whose determination uses the Purposive technique. In addition, in the data collection technique in this study through observation, interviews, and documentation. With the method of data analysis with three steps, data condensation, data display, and conclusion drawing and verification. Based on the results of the study using the Edward III theory, it was concluded that the livestock control program policy in Sigi District, Central Sulawesi Province had not been carried out optimally. This is caused by several aspects that are still not working well, such as in the aspect of communication which shows that the distribution of all information related to policies to the community is still considered to be running less optimally. In the aspect of resources, it is also not going well because the number of policy implementers is still minimal, with relatively minimal human resources, of course it is very difficult to accommodate all livestock control activities in a number of sub-districts in Sigi Regency. In addition, the condition of the resources in the form of supporting facilities for Livestock Control activities is still considered to be inadequate. But besides that also in the other two aspects namely disposition and bureaucratic structure has been running quite well, where the implementers of the policy have a high commitment in carrying out their duties, implementing policies which in this case are the Civil Service Police Unit of Sigi Regency guided by clear regulations namely Perda Number 1 of 2017 concerning Animal Control, in the dissemination or distribution of responsibilities of this policy has also been running well and according to their respective duties and functions in implementing this policy.